An Appraisal of the European Union Legal Framework on Illicit Firearms Trafficking after Directive 2017/853/EU (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
This article examines European Union legislation on civilian firearms currently in place. This is with the aim of assessing its effectiveness in preventing and suppressing illicit firearms trafficking, which, in recent years, has considerably contributed to the growing threats of terrorism and transnational organized crime in Europe. The author contends that, notwithstanding undeniable progress, especially after the entry into force of Directive 2017/853/EU, the European Union regulatory framework still requires some steps forward in order to comprehensively tackle illicit firearms trafficking.Keywords: illicit trafficking, firearms, Directive 2017/853/EU, transnational organized crime, terrorism